N7-Methylguanosine Regulatory Genes Profoundly Affect the Prognosis, Progression, and Antitumor Immune Response of Hepatocellular Carcinoma - Zhou, Kexiang; Yang, Jiaqun; Li, Xiaoyan; Xiong, Wei; Zhang, Pengbin; Zhang, Xuqing (Frontiers in Surgery, 2022)
Background Hepatocellular carcinoma (HCC) is a common abdominal cancer with poor survival outcomes. Although there is growing evidence that N7-methylguanosine (m7G) is closely associated with tumor prognosis, development and immune response, few studies focus this topic. Methods The novel m7G risk signature was constructed through the Lasso regression analysis. Its prognostic value was evaluated through a series of survival analyses and was tested in ICGC-LIRI, GSE14520 and GSE116174 cohorts. CIBERSORT, ssGSEA and ESTIMATE methods were applied to explore the effects of m7G risk score on tumor immune microenvironment (TIM). GSEA method was used to evaluate the impacts of m7G risk score on glycolysis, ferroptosis and pyroptosis. HPA database was used to clarify the histological expressions of five m7G signature genes. The biofunctions of NCBP2 in hepatocellular cancer (HC) cells were confirmed through qPCR, CCK8, and Transwell assays. Results Five m7G regulatory genes comprised the novel risk signature. m7G risk score was identified as an independent prognostic factor of HCC and could increase the making-decision benefit of traditional prognostic models. Besides, we established a nomogram containing clinical stage and m7G risk score to predict the survival rates of HCC patients. The prognostic value of m7G model was successfully validated in ICGC and GSE116174 cohorts. Moreover, high m7G risk led the decreased infiltration level of CD8+ T cells, whereas increased that of Tregs and macrophages. The glycolysis and pyroptosis process enriched in the HCC patients with high m7G risk. Finally, overexpression of NCBP2 could promote the proliferation, migration, and invasion of HC cells. Conclusions m7G risk score was closely related to the prognosis, anti-tumor immune process, glycolysis, and malignant progression of HCC. NCBP2 has the pro-oncogenic abilities, showing promise as a novel treatment target.